Diepoxy- Versus Glutaraldehyde-Treated Xenografts: Outcomes of Right Ventricular Outflow Tract Reconstruction in Children. Issue 1 (January 2020) - Nichay, Nataliya R.; Zhuravleva, Irina Y.; Kulyabin, Yuriy Y.; Zubritskiy, Alexey V.; Voitov, Alexey V.; Soynov, Ilia A.; Gorbatykh, Artem V.; Bogachev-Prokophiev, Alexander V.; Karaskov, Alexander M.
Background: Xenografts used for right ventricular outflow tract (RVOT) reconstruction are typically treated with glutaraldehyde. However, potential benefit of epoxy treatment was demonstrated in experimental studies. We aimed to compare diepoxy-treated bovine pericardial valved conduits (DE-PVCs) and glutaraldehyde-treated bovine pericardial valved conduits (GA-PVCs) for RVOT reconstruction in pediatric patients. Methods: Between 2002 and 2017, 117 patients underwent RVOT reconstruction with PVC in single center: DE-PVC group, n = 39; and GA-PVC group, n = 78. After performing propensity score analysis (1:1) for the entire sample, 29 patients from the DE-PVC group were matched with 29 patients from the GA-PVC group. Results: There were no conduit-related deaths. In the DE-PVC group, the freedom from conduit failure was 90.9% at four years and 54.3% at eight years postoperatively. In the GA-PVC group, it was 46.3% and 33.1%, respectively. The difference was significant ( P = .037). Conduit failure was typically caused by stenosis in both groups. In the DE-PVC group, the main cause of stenosis was xenograft calcification (27.6%); while in the GA-PVC group, it was mostly due to neointimal proliferation (25.0%) and, less often, calcification (14.3%). Conduit thrombosis was the cause of replacement in 6.9% of patients from the GA-PVC group. Conclusions: Diepoxy-treated bovine pericardial valved conduit is a suitable alternative to GA-PVC for RVOT reconstruction in pediatric patients. Diepoxy-treated bovine pericardial valved conduits may be less prone to conduit failure and more resistant to neointimal proliferation and conduit thrombosis than GA-PVCs.